Penguatan Digital Marketing Berbasis Artificial Intelligence Bagi Produk Lokal UMKM - Fatihanursari Dikananda; Edi Wahyudin; Odi Nurdiawan; Rudi Kurniawan (CV. Multi Kreasi Media, 2025)
Micro, Small, and Medium Enterprises (MSMEs) play a significant role in regional economic development but continue to face challenges in implementing digital marketing strategies. This community service program aimed to improve MSMEs' capabilities through mentoring on Artificial Intelligence (AI)-based digital marketing for five MSMEs in Cirebon City. The implementation included needs assessment, digital marketing training, AI utilization workshops, implementation assistance, and monitoring and evaluation. The results demonstrated improvements in social media management, content planning, AI-assisted copywriting, and digital promotional activities. The program enhanced participants' digital competencies and supported sustainable improvements in the competitiveness of local products.